Variáveis qualitativas da pulverização em feijão, Bidens pilosa E Brachiaria plantaginea - Rodrigues, Andreia Cristina Peres [UNESP]; Martins, Dagoberto [UNESP]; Costa, Neumarcio Vilanova da; Cardoso, Leonildo Alves [UNESP]; Domingos, Vanessa David [UNESP] (Editora da Universidade Federal de Lavras (UFLA), 2010)
Conduziu-se este trabalho, com o objetivo de avaliar a qualidade da deposição da calda de pulverização em plantas de feijão (Phaseolus vulgaris L.), Bidens pilosa L. e de Brachiaria plantaginea (Link) Hitchc. presentes na linha e entrelinha da cultura. Foi utilizado como traçador o corante Azul Brilhante FDC-1 (500 ppm). Utilizaram-se cinco pontas de pulverização: jato plano (XR 110015 VS e XR 11002 VS), jato plano duplo (TJ60 11002 VS) e jato cônico (TX-6 VS e TX-8 VS) e dois volumes de aplicação 150 e 200 L ha-1. O delineamento utilizado foi de blocos ao acaso, com 4 repetições. Foram amostradas 25 plantas em cada parcela/repetição, de plantas de feijão e plantas daninhas presentes na linha e na entrelinha da cultura. Após a aplicação, as plantas foram coletadas e lavadas em água destilada para quantificação do traçador em espectrofotômetro. Os dados ajustaram-se à curva de regressão pelo modelo de Gompertz. Os resultados evidenciaram que: para as plantas de feijão as pontas XR 110015 e TJ60 proporcionaram as deposições mais uniformes, nos volumes de 150 e 200 L ha-1, respectivamente; a ponta TX-6 no volume de 150 L ha-1 apresentou melhor uniformidade de distribuição para ambas as espécies de plantas daninhas presentes na linha da cultura; para as plantas daninhas presentes na entrelinha, no volume de 150 L ha-1, destacaram-se as pontas XR 110015 e TJ60 11002 para B. pilosa e B. plantaginea, respectivamente, no volume de 200 L ha-1 destacou-se a ponta TX-8 para ambas as espécies.

The objective of the present study was to evaluate the deposition quality of spray solution in common bean plants (Phaseolus vulgaris L.), Bidens pilosa L. and Brachiaria plantaginea (Link) Hitchc., present in the crop row and spacing row. Brilliant blue FDC - 1 was used as a tracer solution (500 ppm). Five nozzles were used: flat fan nozzle (XR 110015 VS and XR 11002 VS), double flat fan nozzle (TJ60 11002 VS) and cone nozzle (TX-6 VS and TX-8 VS), and two application volumes: 150 and 200 L ha-1. A randomized blocks design was used, with four replications. 25 plants were sampled for replication in each plot, common beans as well as weeds in crop row and spacing row. After the application, the plants were collected and washed in distilled water for tracer quantification in spectrophotometer. The data adjusted to the regression curve according to the Gompertz model. The results showed that, for the common bean plants, XR 110015 and TJ60 nozzles had provided the most uniform depositions in 150 and 200 L ha-1 application volume, respectively; the nozzle in the volume of 150 L ha-1 had a more uniform distribution for both the species of harmful plants present in the crop line; for the weeds present in the crop row in a volume of 150 L ha-1 the best performances were presented by the XR 110015 nozzle for B. pilosa and the TJ60 nozzle for B. plantaginea. For the volume of 200 L ha-1 , the TX-8 nozzle presented the best performance for both species.
Qualitative variables of spraying in common beans, Bidens pilosa and Brachiaria plantaginea
Keywords: Phaseolus vulgaris; picão-preto; Bidens pilosa; capim-marmelada; Brachiaria plantaginea; bico; volume; Common bean; Phaseolus vulgaris; hairy beggarticks; Bidens pilosa; alexandergrass; Brachiaria plantaginea; nozzle; volume